Analisis Pengetahuan, Sikap, dan Perilaku Penggunaan Antibiotik pada Mahasiswa Fakultas Kedokteran Universitas Jember - Emeralda Austin Nabila (Fakultas Kedokteran, 2025)
Antibiotics are one of a drugs that must be used rationally. Irrational use of antibiotics can cause antibiotic resistance. Antibiotics uses are influenced by knowledge, attitudes and practice. Medical students, who will be a doctor must have a good knowledge, attitudes and practice when using antibiotic. This study aims to analyze the knowledge, attitudes and practice of antibiotic uses among medical students at University of Jember. This study used an analytic observational method with a cross-sectional design. A total of 277 respondent participated using quota sampling technique. Questionnaire were distributed online. Data were analyzed using Chi-square and Spearman test. A p<0.05 is considered significant. The results showed that most of the clinical student had a good knowledge, attitude, and practice in using antibiotics, while pre-clinical student had a good attitude and practice, but sufficient knowledge regarding antibiotic use. Chi-square test results showed a significant difference in knowledge (p=0.000) and attitudes (p=0.000), but no significant difference in practice (p=0.105) between pre-clinical and clinical student regarding antibiotic use. Spearman test results showed a significant relationship between knowledge towards attitudes both in pre-clinical (p=0.000) and clinical student (p=0.036), as well as attitudes towards practice in both groups (p=0.001). However, there is a significant relationship between knowledge towards practice in clinical students (p=0.001), but not in pre-clinical students (p=0.434) regarding antibiotic use. Differences in forms of learning and other factors such as beliefs, personal references, resources, and culture between pre-clinical and clinical students could make a different knowledge, attitudes, and practice regarding antibiotic use between two groups.
Reuploud Repository hasyim Mei 2026 ; FINALISASI oleh Agus 2026 Juni 17
Keywords: knowledge; attitude; practice; antibiotic use; medical student